Crateva formosensis (Jacobs) B. S. Sun, (Capparaceae Juss.) - A new record for flora of Vietnam - Thuong, Sy Danh; Bach, Tran The (Academia Journal of Biology, 2012)
We have found that Crateva formosensis (Jacobs) B. S. Sun has also distributed in Vietnam, with specimens collected in Tra Linh district, Cao Bang province. The specimens are preserved in HN Herbarium, Institute of Ecology and Biological Resources. This species is closely related to Crateva trifoliata (Roxb.) B. S. Sun but differs in characters: size and apex of leaflet blade and number of stamens, hence, Crateva formosensis (Jacobs) B. S. Sun is a new record for the flora of Vietnam. The main characters of Crateva formosensis: shrub or tree, 2-21m tall, with flowers before having leaves or when having young leaves. Twigs with flowers: leaflet blades ovate to obovate, 10-11.5 ´ 4-5 cm, dried leaves green-grey color to green-brown; twigs without flowers: leaflet blade 13-15 ´ 6 cm, apex acuminate to long acuminate. Inflorescences 10-15 flowered, pedicel 2.5-4 cm. Sepals 4, oblong. Petals yellow, claw 4 mm, blade elliptic. Stamens 10-15. Gynophore 2.4-3.2 cm. Ovary ovate. Fruits circular to oval, red to red-brown, smooth. Seeds small, brown. Loc. class.: Formosa. Holotypus: E. H. Wilson 11114 (K). Ecology and Biology: Flowering June - July, fruting August - January. In valley, near stream, dense forest and coastal region to 400 m alt.. Distribution: Cao Bang (Tra Linh). Also in China, Japan. Studied specimens: Cao Bang (Tra Linh), W17463, VN 478 (HN).